The relationship between oil price and the performance of stock market in Malaysia case study: Kuala Lumpur Composite Index (KLCI) / Nor Farisha Ismail - Ismail, Nor Farisha (Faculty of Business and Management, 2011)
This study tries to investigate the relationship between oil prices and stock market in Malaysia. The performance may be influence by many factors, relation with economics of views and perspectives. It may be cause by major macroeconomic variables such as inflation, money supply, exchange rate, industrial production and others. This paper is to provide an analysis of the significance correlation between stock prices and some major macroeconomic variables. Data of monthly oil price (OP) in US, monthly stock price (KLCI) and monthly consumer price index (CPI) as variables in this study. The data is collected for the five years period of 1 January 2006 to 31 December 2010 and used to multiple regression method to examine the significance level of the relationships between dependent and independent variables. The results from this model that this is significant relationship between oil price and stock market with the oil price movement. Furthermore, the analysis also shows inflation has a relationship with stock price but there is no significant result due to the more significant on other macroeconomic variable. These results further our understanding of the interaction between oil prices and share prices and should be of use to investors, regulator, managers, and policy maker.